De Bandoengsche Gasfabriek: Perkembangan industri gas dan modernisasi keamanan pangan di Kota Bandung (1921-1942) - Mutawally, Anwar Firdaus; Dienaputra, Reiza D. (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
This study aims to trace the development of the gas factory in Bandung and its influence on the modernization of hygiene in the city of Bandung during the colonial period. Previous studies on colonial Bandung have rarely discussed hygiene or the gas factory. In addition, there has been no research linking the emergence of gas technology as a driver of improving food hygiene in the Dutch East Indies. Therefore, there needs to be a historical study that discusses gas technology with the setting of the place in colonial Bandung. The method used in this study is the historical method through four stages, namely heuristics, criticism, interpretation, and historiography. Historical data were obtained through tracing primary and secondary sources. The results of the study indicate that the background to the emergence of the gas factory in Bandung was driven by the scarcity of firewood and the colonial government's efforts to improve unhealthy food hygiene conditions. During its operation from 1921 to 1942, the gas factory became a provider of cooking fuel for the residents of Bandung. This study argues that the presence of the gas factory is correlated with improvements in food hygiene in the city of Bandung.